Estrategias de marketing y la rentabilidad en la pandemia del covid -19. - Matute Prospel, Patsy Betzabeth; Belduma Ajila, Jordy Alexander (Universidad Técnica de Machala, 2022)
The general objective of this project is to analyze marketing strategies through the application of an adequate methodology to determine their impact on profitability in the period 2020 time of COVID-19 of the business "MEGACREDITO JB" located in the city of Pasaje, province of El Oro. In chapter I, the approach to the problem is presented based on the object of study, research problem, justification and objectives, while in chapter II the systematic review of the literature will be studied based on the system of citation and referentiality. Chapter III will be based on the analysis of the methodology for data collection proceeding to chapter IV where the obtaining of the results and the discussion will be determined; finally in chapter V the conclusions and recommendations will be presented. This will be carried out according to the information obtained from the business results statements to calculate the profitability of the 2019-2020 periods, thus obtaining a respective comparison of the strategies used. On the other hand, a marketing plan is proposed that allows the business to obtain greater benefits in the market.
El presente proyecto tiene como objetivo general analizar las estrategias de marketing mediante la aplicación de una metodología adecuada para la determinación de su incidencia en la rentabilidad en el periodo 2020 tiempo del COVID-19 del negocio “MEGACREDITO JB” ubicado en la ciudad de Pasaje, provincia de El Oro. En el capítulo I, se presenta el planteamiento del problema en base al objeto de estudio, problema de la investigación, justificación y objetivos mientras que en el capítulo II se estudiará la revisión sistemática de la literatura en base al sistema de citación y referencialidad. El capítulo III se basará en el análisis de la metodología para la recolección de datos procediendo al capítulo IV donde se determinará la obtención de los resultados y la discusión; finalmente en capítulo V se presentará las conclusiones y recomendaciones. Esto se llevara a cabo de acuerdo a la información obtenida de los estados de resultados del negocio para calcular la rentabilidad de los periodos 2019-2020 obteniendo así una respectiva comparación de las estrategias usadas. Por otro lado, se propone un plan de marketing que le permita al negocio obtener mayores beneficios en el mercado.
Keywords: ESTRATEGIAS; MARKETING; COVID-19; RENTABILIDAD